Enhancing water use efficiency and crop yield through effective nutrient management and mulching practices - KUMAR, YOGESH; KUMAR, MUNISH; KUMAR, SARVESH; KUMAR, KAUSHAL; KUMAR, SANJIV; PRAJAPATI, BIMLESH KUMAR; YADAV, SANJAY (Journal of Soil and Water Conservation, 2025)
The present investigation was performed with twenty-one treatment combinations in split-plot design during the summer seasons of 2022 and 2023 at the Soil Conservation and Water Management Farm, Chandra Shekhar Azad University of Agriculture & Technology, Kanpur. Three Mulching practices M1- No mulch and M2- Dust mulch, M3- Rice straw mulch allotted in main plot along with seven different integrated nutrient management practices: N1- 50% RDF+25% N vermicompost/ ha, N2- 75% RDF+25% N vermicompost/ha, N3- 100% RDF+25%N vermicompost/ha, N4- 50% RDF+25% N FYM /ha, N5-75% RDF+25% N FYM/ha, N6-100% RDF+25% N FYM/ha, and N7 - 100% RDF in sub-plot. The results indicate that the combination of rice straw mulch with 100% RDF along with 25% vermicompost significantly achieved the highest growth parameters, including water use, water use efficiency, grain yield, stover yield, biological yield, and harvest index.